ANALISIS PERFORMANSI METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) DALAM PENGENDALIAN PERSEDIAAN SUSU - Tajrin Tajrin; Hendra Hendra; Juan Fernando Gurning (Politeknik Bisnis Indonesia, 2024)
This study aims to address the issue of milk inventory control at PT. Indodairy Continental by applying the Autoregressive Integrated Moving Average (ARIMA) method. The uncertainty in milk demand, influenced by changes in consumer consumption patterns and market fluctuations, poses challenges in accurate production and distribution planning. This research uses historical milk sales data from the past several years to build an ARIMA model. The data undergoes several steps, including data collection and plotting, stationarity testing using ACF and PACF, differencing, and parameter estimation of the ARIMA model. The analysis results indicate that the data is stationary, and the ARIMA (1,0,0) model is selected as the best model based on the significance test. This model is used to forecast milk sales for the next six months. The predictions indicate an increase in monthly sales, allowing the company to optimize production and distribution processes, reduce costs, and improve customer satisfaction.